Bond behavior between steel bar and engineered cementitious composite (ECC) considering lateral FRP confinement: Test and modeling. (15th October 2019) - Zhou, Yingwu; Fu, Huankai; Li, Pengda; Zhao, Debo; Sui, Lili; Li, L.
Abstract: Engineered cementitious composite (ECC) exhibits good post-cracking resistance and ductility and its unique properties make it a viable material for increasing structural performance under severe loading conditions. To understand the bond behavior between the ECC and steel bar, direct pullout tests were conducted in this paper. A comprehensive analysis was carried out on effects of ECC strength, steel bar diameter, and fiber reinforced polymer (FRP) confinement on steel bar-ECC bonding behavior. Based on the experimental data, performances of existing bond slip models for steel bar-ECC are evaluated and a new model with improved accuracy is proposed. The proposed model considers the influence of FRP confinement on bond-slip behavior.